TiN-SiN2O ceramic modified C / C-SiC brake material and preparation method thereof

By adding Si and TISI2 powder to C/C-SIC braking materials, the Tin-SIN2O and SIC ceramic phase is generated to achieve the improvement of the friction and wear of the material and the improvement of the mechanical properties of the material. , Realize more efficient braking materials.

CN119371220AActive Publication Date: 2025-01-28NORTHWESTERN POLYTECHNICAL UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411568568.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-28
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing C/C-SiC brake materials have shortcomings in friction and wear properties and mechanical properties, and have a long preparation cycle and high cost, which limits their wide application.

Method used

By adding pinks such as Si and TISI2 to the raw materials, the Tin-SIN2O and SIC ceramic phase are used to use reactions, so that carbonized-ceramic-density-density is completed in a thermal treatment, thereby shortening the preparation cycle, improving the mechanical performance and reducing wear rates.

Benefits of technology

It has significantly improved the friction and wear performance and mechanical performance of the material, shorten the preparation cycle, and is expected to reduce costs. It solves the problems of the existing C/C-SIC materials that cannot take into account the problems of excellent friction and wear performance, mechanical properties and shorter preparation cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371220A_ABST
    Figure CN119371220A_ABST
Patent Text Reader

Abstract

The invention discloses a TiN-SiN2O ceramic modified C / C-SiC brake material and a preparation method thereof, and belongs to the technical field of friction brake material preparation. According to the material, TiN-SiN2O ceramic is adopted to modify a C / C-SiC material. Powder such as Si and TiSi is added into raw materials, TiN-SiNO and SiC ceramic phases are generated through a reaction, carbonization, ceramization and densification are completed in one-time heat treatment, and therefore the preparation period is shortened, meanwhile, the mechanical property is improved, the wear rate is reduced, and cost is expected to be reduced; the preparation method is used for solving the problem that excellent friction and wear properties, mechanical properties and a short preparation period of existing C / C-SiC cannot be considered at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of friction brake material preparation, and specifically relates to a TiN-SiN2O ceramic modified C / C-SiC brake material and a preparation method thereof. Background Art

[0002] With the development of science and technology, the speed of modern transportation vehicles is increasing, and the requirements for the braking system are also getting higher and higher. The braking materials of vehicles with frequent braking, such as cars, airplanes, high-speed trains, and trucks, have gone through several generations of development. The asbestos friction material that first emerged had the advantages of light weight and low cost, but it was gradually replaced because asbestos is a carcinogen; the powder metallurgy friction material that appeared later had a long service life and high reliability, but its high density and easy bonding at high temperatures limited its use conditions. C / C-SiC friction material is a new type of friction material with a series of excellent comprehensive properties such as high strength, high thermal conductivity, good mechanical properties, and strong environmental adaptability. It inherits the advantages of existing friction materials and makes up for the shortcomings of existing friction materials, which has attracted widespread attention.

[0003] Traditional C / C-SiC materials are composed of carbon fiber, matrix carbon and SiC. Because they only contain SiC ceramic phase, they have problems of insufficient toughness and high wear rate. In addition, the high cost and complicated preparation process limit their wide application. At present, the preparation methods of C / C-SiC materials mainly include chemical vapor infiltration, polymer impregnation and pyrolysis, reactive melt infiltration, etc. Among them, the chemical vapor infiltration method and polymer impregnation and pyrolysis method use the whole felt of continuous fiber as the reinforcement, and the obtained products have excellent mechanical properties. However, due to the alternating distribution of the mesh layer / weft-free cloth, the friction stability of the material reinforced by the whole felt of continuous fiber is relatively low, and the preparation cycle is as long as more than 150 hours. At the same time, the raw material cost of the whole felt of continuous fiber is also high. In contrast, the reactive melt infiltration method has a simple process, and the reinforcement can use the whole felt of continuous fiber or short fiber. The cycle can be shortened to 72 hours compared with the chemical vapor infiltration method and polymer impregnation and pyrolysis method, but there is 5%-15% residual silicon by mass in the products prepared by the reactive melt infiltration method, which has an adverse effect on the overall friction and wear properties and mechanical properties of the material. Therefore, developing a method that can significantly improve the friction and wear performance of the material and have a shorter preparation cycle is crucial to promoting the large-scale application of C / C-SiC brake materials.

[0004] For example, the Chinese patent with the patent publication number CN116354735A discloses a method for rapidly preparing AlN-modified C / C-SiC friction material, in which a uniform mixture of short carbon fibers, phenolic resin, industrial silicon powder and aluminum powder is pressed into a fiber-reinforced resin block, which is then subjected to carbonization and ceramicization heat treatment to obtain a C / C-AlN-SiC friction material. This method has a short densification cycle and low preparation cost, but the wear rate of the material is still 1.277×10 -15 m 3 N -1 m -1 -34.765×10 - 15 m 3 N -1 m -1 It is still high, and the modified component AlN ceramic is easy to hydrolyze, which limits its use conditions. And the Chinese patent with patent publication number CN101493126A discloses a method for manufacturing carbon / ceramic brake linings for industrial brakes. The method first uses a needle punching method to prepare a carbon fiber preform, and then uses a chemical vapor infiltration method to prepare a low-density C / C composite material after high-temperature heat treatment. The C / C composite material is machined after high-temperature heat treatment, and then the C / C material is melt-siliconized in a high-temperature vacuum furnace, and Si reacts with C to form SiC to obtain a C / C-SiC brake material. This method combines chemical vapor infiltration and reactive infiltration. The prepared C / C-SiC brake material has high mechanical properties, but the material still contains a small amount of residual silicon, which affects its friction and wear performance. The preparation cycle is as long as 130-300 hours, and the cost of the raw material continuous fiber used is relatively high.

[0005] In summary, how to improve the friction and wear properties and mechanical properties of C / C-SiC materials while shortening the preparation cycle and reducing costs is a technical problem to be solved by those skilled in the art. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a TiN-SiN2O ceramic modified C / C-SiC brake material and a preparation method thereof, by adding Si and TiSi2 powders and the like to the raw materials, utilizing the reaction to generate TiN-SiN2O and SiC ceramic phases, so that carbonization-ceramicization-densification are completed in one heat treatment, thereby shortening the preparation cycle, while improving the mechanical properties and reducing the wear rate, and is expected to reduce the cost, so as to solve the problem that the excellent friction and wear performance, mechanical properties and shorter preparation cycle of the existing C / C-SiC cannot be taken into account at the same time.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: On one hand, the present invention provides a TiN-SiN2O ceramic modified C / C-SiC brake material, wherein the TiN-SiN2O ceramic modified C / C-SiC brake material uses TiN-SiN2O ceramic to modify C / C-SiC material.

[0008] The TiN-SiN2O ceramic modified C / C-SiC brake material is made of the following raw materials by volume percentage: 10-20% TiSi2 powder, 7-20% graphite powder, 15-20% phenolic resin powder, 10-13% SiC powder, 20-30% Si powder and 15-20% chopped carbon fiber.

[0009] In one embodiment, the TiN-SiN2O ceramic modified C / C-SiC brake material includes TiN ceramic, SiN2O ceramic and SiC ceramic. The TiN-SiN2O ceramic modified C / C-SiC brake material has a compressive strength of 270-290 MPa, a bending strength of 120-130 MPa, and a wear rate reduced to 2.05×10 -16 m 3 N -1 m -1 .

[0010] The present invention also provides a method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material, comprising the following steps: The TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder are uniformly mixed to obtain a mixed powder; short-cut carbon fibers are added into anhydrous ethanol, stirred, dispersed and dried to obtain dispersed fibers; The mixed powder and the fiber are mixed evenly to obtain the fiber mixed powder; the fiber mixed powder is molded to obtain the fiber reinforced resin block; curing the fiber reinforced resin block to obtain a cured fiber reinforced resin block; The cured fiber reinforced resin block is heat treated in a nitrogen atmosphere to obtain a TiN-SiN2O ceramic modified C / C-SiC brake material.

[0011] In one embodiment, the TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder are ball-milled and mixed in a planetary ball mill, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 2-3 h.

[0012] In one embodiment, the dispersion is performed under an ultrasonic power of 60-100 W, and the dispersion time is 10-15 min.

[0013] In one embodiment, the drying is performed at a temperature of 50-80° C., and the drying time is 2-4 hours.

[0014] In one embodiment, the molding temperature is 160-190° C., the molding pressure is 7-10 MPa, and the molding time is 60-120 min.

[0015] In one embodiment, the curing process is a step-by-step curing process, and the specific process is as follows: heating to 160° C. and keeping it for 3 hours, then heating to 180° C. and keeping it for 3 hours, and finally heating to 220° C. and keeping it for 2 hours.

[0016] In one embodiment, the heat treatment is performed under a carrier gas atmosphere, the carrier gas atmosphere is a nitrogen atmosphere, and the flow rate of the carrier gas is 80-120 mL / min.

[0017] In one embodiment, the heat treatment process is as follows: heating to 900-1000°C at a heating rate of 1-5°C / min, keeping warm for 1-2h, then heating to 1400-1500°C at a heating rate of 1-5°C / min, keeping warm for 2-3h, then cooling to 250-300°C at a cooling rate of 7-10°C / min and then cooling to room temperature with the furnace.

[0018] Compared with the prior art, the present invention has the following beneficial effects: On one hand, the present invention provides a TiN-SiN2O ceramic modified C / C-SiC brake material. TiSi2 powder and Si powder in the raw materials react with carrier gas N2 to generate ceramics such as TiN and SiN2O, which can fill the pores generated by resin carbonization and improve the density of the material, which is equivalent to the density of the material prepared by the reaction infiltration method; and because there are multiple ceramics such as TiN, SiN2O and SiC, the deficiency of single SiC ceramic is compensated, TiN and SiN2O ceramics have higher toughness and lower hardness than SiC, the addition of TiN and SiN2O is conducive to reducing excessive abrasive wear of the material caused by excessive hardness during friction, and the improvement of toughness is conducive to improving the mechanical properties of the material; and the thermal stability of TiN and SiN2O ceramics is higher than that of SiC, which is conducive to reducing oxidation wear and fatigue wear of the material at high temperature. SiC powder is added to the raw material. SiC powder can act as a sintering aid, which is conducive to the reaction during the heat treatment process. SiC powder can reduce the volume shrinkage of resin carbonization and silicon-carbon reaction, prevent large internal stress in the material, and can also be stably present in the material as an inert filler. It has a good combination with SiC generated by the silicon-carbon reaction and acts as a ceramic phase to improve performance. Graphite powder is added to the raw material. Graphite powder has low hardness and can be used as a lubricating phase to adjust the friction coefficient of the material to avoid high wear rate caused by excessive hardness and friction coefficient of the material. It can also act as a carbon source for the reaction of Si and C, reducing the reaction of carbon fiber and Si, thereby reducing the damage of carbon fiber. The material reinforcement uses short carbon fiber, which is evenly distributed in the material and randomly oriented in the material. Compared with the material reinforced by the fiber integral felt, the friction stability is relatively low due to the alternating distribution of the mesh layer / weft-free cloth. The short carbon fiber is evenly distributed in the material and randomly oriented, so it has better friction stability. And the cost of short carbon fiber is only 30% of that of the continuous fiber integral felt.

[0019] The material has excellent mechanical properties and low wear rate. The compressive strength of the material is increased to 270-290MPa, the bending strength is increased to 120-130MPa, and the wear rate is reduced to 2.05×10 -16 m 3 N -1 m -1 .

[0020] On the other hand, the present invention also provides a method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material, wherein the above raw materials are sequentially subjected to curing treatment and heat treatment, and the carbonization-ceramicization-densification process is completed in one heat treatment. Compared with the existing process, compared with the existing technology, the cycle can be shortened from more than 150 hours to about 30 hours, and there is no need for more complicated processes, which significantly reduces the cost of manpower and equipment use. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a cross-sectional SEM image of TiN-SiN2O ceramic modified C / C-SiC brake material; (a) is a low magnification; (b) is a high magnification; Figure 2 is the XRD spectrum of TiN-SiN2O ceramic modified C / C-SiC brake material; wherein (a) is Example 1 and Example 2; (b) is Example 3 and Comparative Example 1; Figure 3 are the mechanical properties of TiN-SiN2O ceramic modified C / C-SiC brake materials; where (a) is the bending strength; (b) is the compressive strength; Figure 4 It is the tribological properties of TiN-SiN2O ceramic modified C / C-SiC brake material; among them, (a) is the comparison chart of friction coefficient change; (b) is the friction coefficient and wear rate. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0024] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0025] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0027] The present invention provides a TiN-SiN2O ceramic modified C / C-SiC brake material and a preparation method thereof. The TiSi2 powder and Si powder added to the raw materials react with the carrier gas N2 to generate ceramics such as TiN and SiN2O, which increases the density of the material and reduces the porosity of the material, thereby obtaining a multi-component ceramic co-modified C / C-SiC composite material, thereby reducing the wear rate and improving the mechanical properties of the material. Secondly, a preform is prepared by a rapid molding method, and the carbonization-ceramicization-densification process of the preform into a product is completed in one heat treatment. Compared with the existing process, the cycle is significantly shortened and the cost of manpower and equipment use is reduced.

[0028] On one hand, the present invention provides a TiN-SiN2O ceramic modified C / C-SiC brake material, wherein the TiN-SiN2O ceramic modified C / C-SiC brake material uses TiN-SiN2O ceramic to modify the C / C-SiC material; the raw materials for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material are as follows, by volume percentage: 10-20% TiSi2 powder, 7-20% graphite powder, 15-20% phenolic resin powder, 10-13% SiC powder, 20-30% Si powder and 15-20% chopped carbon fiber.

[0029] The compressive strength of the TiN-SiN2O ceramic modified C / C-SiC brake material is 270-290MPa, the bending strength is 120-130MPa, and the wear rate is reduced to 2.05×10 -16 m 3 N -1 m -1 .

[0030] Another aspect of the present invention also provides a method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material, comprising the following steps: The TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder are uniformly mixed to obtain a mixed powder; short-cut carbon fibers are added into anhydrous ethanol, stirred, dispersed and dried to obtain dispersed fibers; The mixed powder and the fiber are mixed evenly to obtain the fiber mixed powder; the fiber mixed powder is molded to obtain the fiber reinforced resin block; curing the fiber reinforced resin block to obtain a cured fiber reinforced resin block; The cured fiber reinforced resin block is heat treated to obtain a TiN-SiN2O ceramic modified C / C-SiC brake material.

[0031] In a specific embodiment, the above preparation method specifically comprises the following steps: Step 1: Weigh TiSi2 powder A, graphite powder B, phenolic resin powder C, SiC powder D, Si powder E, and chopped carbon fiber F.

[0032] Step 2: Evenly mix TiSi2 powder A, graphite powder B, phenolic resin powder C, SiC powder D, and Si powder E to obtain mixed powder G.

[0033] Step 3: Add the chopped carbon fiber F into anhydrous ethanol, stir thoroughly, disperse, and dry to obtain dispersed fiber H.

[0034] Step 4: Mix the mixed powder G and the fiber H in a high-speed grinding mill to obtain fiber mixed powder I.

[0035] Step 5: Add the fiber mixed powder I into a self-made mold and perform molding in a molding press to obtain a fiber reinforced resin block J.

[0036] Step 6: The block J is cured in an oven to obtain a cured fiber reinforced resin block K.

[0037] Step 7: Heat-treating the block J in a carrier gas atmosphere, and heating and cooling according to a heating curve to obtain a C / C-TiN-SiN2O-SiC composite material.

[0038] In the above step 1, by volume percentage: TiSi2 powder A accounts for 10-20%; graphite powder B accounts for 7-20%; phenolic resin powder C accounts for 15-20%; SiC powder D accounts for 10-13%; Si powder E accounts for 20-30%; short-cut carbon fiber F accounts for 15-20%.

[0039] In the above step 2, the mixing is to place TiSi2 powder A, graphite powder B, phenolic resin powder C, SiC powder D, and Si powder E in a planetary ball mill for mixing, with a ball milling speed of 300-400 r / min and a ball milling time of 2-3 h.

[0040] In the above step 3, the dispersion is carried out at an ultrasonic power of 60-100 W for 10-15 min; and the drying / drying is carried out at 50-80° C. for 2-4 h.

[0041] In the above step 4, the mixing times are 6-10 times.

[0042] In the above step 5, the molding temperature is 160-190° C., the molding pressure is 7-10 MPa, and the molding time is 60-120 min.

[0043] In the above step 6, the curing process is a step-by-step curing process, and the specific process is as follows: heating to 160°C and keeping it for 3 hours, then heating to 180°C and keeping it for 3 hours, and finally heating to 220°C and keeping it for 2 hours.

[0044] In the above step 7, the heat treatment carrier gas is N2, and the carrier gas flow rate is 80-120mL / min; the above temperature rise curve is to heat up to 900-1000℃, keep it for 1-2h, then heat up to 1400-1500℃, keep it for 2-3h, cool down to 250-300℃ and then cool down to room temperature with the furnace. The heating rate is 1-5℃ / min, and the cooling rate is 7-10℃ / min.

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0047] Embodiment 1: A method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material comprises the following steps: Step 1: Calculated by volume percentage, TiSi2 powder accounts for 20%, graphite powder accounts for 10%, phenolic resin powder accounts for 20%, SiC powder accounts for 10%, Si powder accounts for 20%, and chopped carbon fiber accounts for 20%. The corresponding weights are as follows: Weigh 27.10g TiSi2 powder, 6.78g graphite powder, 10.16g phenolic resin powder, 10.85g SiC powder, 15.85g Si powder, and 11.86g chopped carbon fiber for standby use.

[0048] Step 2: Put the weighed TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder into a ball mill, set the speed to 400r / min, mix the powders with a planetary ball mill for 2h and set aside.

[0049] Step 3: Add the weighed chopped carbon fiber into 100 mL of anhydrous ethanol and stir for 15 min. Set the ultrasonic disperser power to 100 W. After dispersing for 10 min, put it into an oven at 50 ° C and dry it for 4 h for standby use.

[0050] Step 4: Mix the powder processed in step 2 with the chopped carbon fiber processed in step 3 in a high-speed mill set at a speed of 23000 r / min, and repeat 6 times, with an interval of 10 minutes each time.

[0051] Step 5: The powder processed in step 4 is molded on a molding machine with a molding pressure of 10 MPa, a molding temperature of 160°C, and a holding time of 60 min to obtain a density of 2.2 g / cm 3 Fiber reinforced resin composite block.

[0052] Step 6: Place the block obtained in step 5 into an oven for curing. The curing process is to keep the temperature at 160°C for 3 hours, then heat it to 180°C for 3 hours, and finally heat it to 220°C for 2 hours to obtain a cured fiber reinforced resin block.

[0053] Step 7: Place the block obtained in step 6 in a tubular heat treatment furnace for heat treatment. The heat treatment carrier gas is N2 and the carrier gas flow rate is 120 mL / min. The heating curve is to increase the temperature from room temperature to 900°C at a heating rate of 1°C / min, keep it warm for 2 hours, so that the phenolic resin in the material is converted into resin carbon, increase the temperature from 900°C to 1400°C at a heating rate of 5°C / min, keep it warm for 3 hours, and cool it from 1400°C to 300°C at a cooling rate of 7°C / min. Then cool it to room temperature with the furnace to convert the TiSi2 powder and Si powder in the material into TiN, SiN2O and SiC ceramics, and obtain a C / C-TiN-SiN2O-SiC composite material with a material density of 2.29 g / cm 3 .

[0054] See also Figure 1 , SEM image of the cross section of TiN-SiN2O ceramic modified C / C-SiC brake material. It can be seen from the figure that different phases are evenly distributed on the cross section, among which the black and dark gray phases are graphite, resin carbon and carbon fiber, the medium gray phase is SiC, the light gray is TiN, and the white is SiN2O. There is no crack defect on the cross section. Figure 2 (a), XRD spectrum of TiN-SiN2O ceramic modified C / C-SiC brake material. It can be seen that C, TiN, SiN2O and SiC were detected in the material, indicating that the C / C-TiN-SiN2O-SiC composite material was successfully prepared. Figure 3 and Figure 4The bending strength of the material is 130.88MPa, the compressive strength is 292.56MPa, the dynamic friction coefficient is 0.553, and the wear rate is 25.24×10 -16 m 3 N -1 m -1 .

[0055] Embodiment 2: A method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material comprises the following steps: Step 1: Calculated by volume percentage, TiSi2 powder accounts for 15%, graphite powder accounts for 15%, phenolic resin powder accounts for 20%, SiC powder accounts for 10%, Si powder accounts for 20%, and chopped carbon fiber accounts for 20%. The corresponding weights are as follows: Weigh 20.33g TiSi2 powder, 10.16g graphite powder, 10.16g phenolic resin powder, 10.85g SiC powder, 15.85g Si powder, and 11.86g chopped carbon fiber for standby use.

[0056] Step 2: Put the weighed TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder into a ball mill, set the speed to 400r / min, mix the powders with a planetary ball mill for 2h and set aside.

[0057] Step 3: Add the weighed chopped carbon fiber into 100 mL of anhydrous ethanol and stir for 15 min. Set the ultrasonic disperser power to 100 W. After dispersing for 10 min, put it into an oven at 50 ° C and dry it for 4 h for standby use.

[0058] Step 4: Mix the powder processed in step 2 with the chopped carbon fiber processed in step 3 in a high-speed mill set at a speed of 23000 r / min, and repeat 6 times, with an interval of 10 minutes each time.

[0059] Step 5: The powder processed in step 4 is molded on a molding machine with a molding pressure of 10 MPa, a molding temperature of 160°C, and a holding time of 60 min to obtain a density of 2.18 g / cm 3 Fiber reinforced resin composite block.

[0060] Step 6: Place the block obtained in step 5 into an oven for curing. The curing process is to keep the temperature at 160°C for 3 hours, then heat it to 180°C for 3 hours, and finally heat it to 220°C for 2 hours to obtain a cured fiber reinforced resin block.

[0061] Step 7: Place the block obtained in step 6 in a tubular heat treatment furnace for heat treatment. The heat treatment carrier gas is N2 and the carrier gas flow rate is 120 mL / min. The heating curve is to increase the temperature from room temperature to 900°C at a heating rate of 1°C / min, keep it warm for 2 hours, so that the phenolic resin in the material is converted into resin carbon, increase the temperature from 900°C to 1400°C at a heating rate of 5°C / min, keep it warm for 3 hours, and cool it from 1400°C to 300°C at a cooling rate of 7°C / min. Then cool it to room temperature with the furnace to convert the TiSi2 powder and Si powder in the material into TiN, SiN2O and SiC ceramics, and obtain a C / C-TiN-SiN2O-SiC composite material with a material density of 2.22 g / cm 3 .

[0062] See also Figure 2 (a), XRD spectrum of TiN-SiN2O ceramic modified C / C-SiC brake material. It can be seen that C, TiN, SiN2O and SiC were detected in the material, indicating that the C / C-TiN-SiN2O-SiC composite material was successfully prepared. Figure 3 and Figure 4 The bending strength of the material is 101.13MPa, the compressive strength is 271.36MPa, the dynamic friction coefficient is 0.356, and the wear rate is 2.05×10 -16 m 3 N -1 m -1 .

[0063] Embodiment 3: A method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material comprises the following steps: Step 1: Calculated by volume percentage, TiSi2 powder accounts for 10%, graphite powder accounts for 20%, phenolic resin powder accounts for 20%, SiC powder accounts for 10%, Si powder accounts for 20%, and chopped carbon fiber accounts for 20%. The corresponding weights are as follows: Weigh 13.55g TiSi2 powder, 13.56g graphite powder, 10.16g phenolic resin powder, 10.85g SiC powder, 15.85g Si powder, and 11.86g chopped carbon fiber for standby use.

[0064] Step 2: Put the weighed TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder into a ball mill, set the speed to 400r / min, mix the powders with a planetary ball mill for 2h and set aside.

[0065] Step 3: Add the weighed chopped carbon fiber into 100 mL of anhydrous ethanol and stir for 15 minutes. Set the power of the ultrasonic disperser to 60 W. After dispersing for 15 minutes, put it into an oven at 80°C and dry it for 2 hours for standby use.

[0066] Step 4: Mix the powder processed in step 2 with the chopped carbon fiber processed in step 3 in a high-speed mill set at a speed of 23000 r / min, and repeat 6 times, with an interval of 10 minutes each time.

[0067] Step 5: The powder processed in step 4 is molded on a molding machine with a molding pressure of 10 MPa, a molding temperature of 160°C, and a holding time of 60 min to obtain a density of 2.15 g / cm 3 Fiber reinforced resin composite block.

[0068] Step 6: Place the block obtained in step 5 into an oven for curing. The curing process is to keep the temperature at 160°C for 3 hours, then heat it to 180°C for 3 hours, and finally heat it to 220°C for 2 hours to obtain a cured fiber reinforced resin block.

[0069] Step 7: Place the block obtained in step 6 in a tubular heat treatment furnace for heat treatment. The heat treatment carrier gas is N2 and the carrier gas flow rate is 120 mL / min. The heating curve is to increase the temperature from room temperature to 900°C at a heating rate of 1°C / min, keep it warm for 2 hours, so that the phenolic resin in the material is converted into resin carbon, increase the temperature from 900°C to 1400°C at a heating rate of 5°C / min, keep it warm for 3 hours, and cool it from 1400°C to 300°C at a cooling rate of 7°C / min. Then cool it to room temperature with the furnace to convert the TiSi2 powder and Si powder in the material into TiN, SiN2O and SiC ceramics, and obtain a C / C-TiN-SiN2O-SiC composite material with a material density of 2.14 g / cm 3 .

[0070] See also Figure 2 (b) XRD spectrum of TiN-SiN2O ceramic modified C / C-SiC brake material. It can be seen that C, TiN, SiN2O and SiC were detected in the material, indicating that the C / C-TiN-SiN2O-SiC composite material was successfully prepared. Figure 3 and Figure 4 The bending strength of the material is 120.13MPa, the compressive strength is 221.24MPa, the dynamic friction coefficient is 0.274, and the wear rate is 14.64×10 - 16 m 3 N -1 m -1 .

[0071] Embodiment 4: A method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material comprises the following steps: Step 1: Calculated by volume percentage, TiSi2 powder accounts for 20%, graphite powder accounts for 7%, phenolic resin powder accounts for 15%, SiC powder accounts for 13%, Si powder accounts for 30%, and chopped carbon fiber accounts for 15%. The corresponding weights are as follows: Weigh 27.10g TiSi2 powder, 4.74g graphite powder, 7.62g phenolic resin powder, 14.09g SiC powder, 23.78g Si powder, and 8.89g chopped carbon fiber for standby use.

[0072] Step 2: Put the weighed graphite powder, phenolic resin powder, SiC powder and Si powder into a ball mill, set the speed to 300 r / min, and mix the powders with a planetary ball mill for 3 hours for standby use.

[0073] Step 3: Add the weighed chopped carbon fiber into 100 mL of anhydrous ethanol and stir for 15 minutes. Set the power of the ultrasonic disperser to 60 W. After dispersing for 15 minutes, put it into an oven at 80°C and dry it for 2 hours for standby use.

[0074] Step 4: Mix the powder processed in step 2 with the chopped carbon fiber processed in step 3 in a high-speed mill set at a speed of 15000 r / min, and repeat 10 times with an interval of 10 minutes each time.

[0075] Step 5: The powder processed in step 4 is molded on a molding machine at a molding pressure of 7 MPa, a molding temperature of 190° C., and a holding time of 120 min to obtain a fiber-reinforced resin composite material block.

[0076] Step 6: Place the block obtained in step 5 into an oven for curing. The curing process is to keep the temperature at 160°C for 3 hours, then heat it to 180°C for 3 hours, and finally heat it to 220°C for 2 hours to obtain a cured fiber reinforced resin block.

[0077] Step 7: Place the block obtained in step 6 in a tubular heat treatment furnace for heat treatment, with N2 as the heat treatment carrier gas and a carrier gas flow rate of 80 mL / min. The heating curve is to increase the temperature from room temperature to 1000°C at a heating rate of 1°C / min, keep the temperature for 1 hour, so that the phenolic resin in the material is converted into resin carbon, increase the temperature from 900°C to 1500°C at a heating rate of 5°C / min, keep the temperature for 2 hours, and decrease the temperature from 1500°C to 250°C at a cooling rate of 10°C / min, and then cool to room temperature with the furnace, so that the TiSi2 powder and Si powder in the material are converted into TiN, SiN2O and SiC ceramics, and obtain a C / C-TiN-SiN2O-SiC composite material.

[0078] Comparative Example 1: A method for preparing a C / C-SiC brake material comprises the following steps: Step 1: Calculated by volume percentage, graphite powder accounts for 20%, phenolic resin powder accounts for 20%, SiC powder accounts for 10%, Si powder accounts for 30%, and short-cut carbon fiber accounts for 20%. The corresponding weights are as follows: Weigh 13.56g of graphite powder, 10.16g of phenolic resin powder, 10.85g of SiC powder, 23.78g of Si powder, and 11.86g of short-cut carbon fiber for standby use.

[0079] Step 2: Put the weighed graphite powder, phenolic resin powder, SiC powder and Si powder into a ball mill, set the speed to 300 r / min, and mix the powders with a planetary ball mill for 3 hours for standby use.

[0080] Step 3: Add the weighed chopped carbon fiber into 100 mL of anhydrous ethanol and stir for 15 minutes. Set the power of the ultrasonic disperser to 60 W. After dispersing for 15 minutes, put it into an oven at 80°C and dry it for 2 hours for standby use.

[0081] Step 4: Mix the powder processed in step 2 with the chopped carbon fiber processed in step 3 in a high-speed mill set at a speed of 15000 r / min, and repeat 10 times with an interval of 10 minutes each time.

[0082] Step 5: The powder processed in step 4 is molded on a molding machine with a molding pressure of 7 MPa, a molding temperature of 190°C, and a holding time of 120 min to obtain a density of 2.00 g / cm 3 Fiber reinforced resin composite block.

[0083] Step 6: Put the block obtained in step 5 into an oven for curing. The curing process is to keep the temperature at 160°C for 3 hours and then increase the temperature to 180°C for 3 hours to obtain a cured fiber reinforced resin block.

[0084] Step 7: Place the block obtained in step 6 in a tubular heat treatment furnace for heat treatment. The heat treatment carrier gas is N2 and the carrier gas flow rate is 80 mL / min. The heating curve is to increase the temperature from room temperature to 1000°C at a heating rate of 1°C / min, keep it warm for 1 hour, so that the phenolic resin in the material is converted into resin carbon, increase the temperature from 900°C to 1500°C at a heating rate of 5°C / min, keep it warm for 2 hours, and cool it from 1500°C to 250°C at a cooling rate of 10°C / min. Then cool it to room temperature with the furnace to convert the Si powder in the material into SiC ceramics to obtain a C / C-SiC composite material with a material density of 2.03 g / cm 3 .

[0085] See also Figure 2 (b) XRD spectrum of C / C-SiC brake material. It can be seen that C and SiC were detected in the material, indicating that the C / C-SiC composite material was successfully prepared. Figure 3 and Figure 4 The bending strength of the material is 45.87MPa, the compressive strength is 188.31MPa, the dynamic friction coefficient is 0.264, and the wear rate is 28.91×10 -16 m 3 N -1 m -1 Compared with Examples 1, 2, and 3 in which TiN-SiN2O ceramics are generated, Comparative Example 1 in which TiN-SiN2O ceramics are not generated has lower compressive strength and bending strength, lower dynamic friction coefficient, higher wear rate, and a large gap in comprehensive performance compared with Examples 1, 2, and 3. Therefore, the TiN-SiN2O ceramic modified C / C-SiC composite material provided by the present invention has excellent performance.

[0086] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A TiN-SiN2O ceramic modified C / C-SiC brake material, characterized in that: The TiN-SiN2O ceramic modified C / C-SiC brake material uses TiN-SiN2O ceramic to modify the C / C-SiC material; The TiN-SiN2O ceramic modified C / C-SiC brake material is made of the following raw materials by volume percentage: 10-20% TiSi2 powder, 7-20% graphite powder, 15-20% phenolic resin powder, 10-13% SiC powder, 20-30% Si powder and 15-20% chopped carbon fiber.

2. The TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 1, characterized in that: The TiN-SiN2O ceramic modified C / C-SiC brake material has a compression strength of 270-290 MPa, a bending strength of 120-130 MPa, and a minimum wear rate of 2.05×10 -16 m 3 N -1 m -1 .

3. A method for preparing a TiN-SiN2O ceramic modified C / C-SiC brake material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder are uniformly mixed to obtain a mixed powder; short-cut carbon fibers are added into anhydrous ethanol, stirred, dispersed and dried to obtain dispersed fibers; Mixing the mixed powder and the fiber to obtain fiber mixed powder; The fiber mixed powder is molded to obtain a fiber reinforced resin block; curing the fiber reinforced resin block to obtain a cured fiber reinforced resin block; The cured fiber reinforced resin block is heat treated in a nitrogen atmosphere to obtain a TiN-SiN2O ceramic modified C / C-SiC brake material.

4. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The TiSi2 powder, graphite powder, phenolic resin powder, SiC powder and Si powder are ball-milled and mixed in a planetary ball mill. The rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 2-3 h.

5. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The dispersion is carried out under an ultrasonic power of 60-100 W, and the dispersion time is 10-15 min.

6. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The drying is carried out at a temperature of 50-80° C., and the drying time is 2-4 hours.

7. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The molding temperature is 160-190° C., the molding pressure is 7-10 MPa, and the molding time is 60-120 min.

8. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The curing process is a step-by-step curing process, and the specific process is as follows: heating to 160° C. and keeping it for 3 hours, then heating to 180° C. and keeping it for 3 hours, and finally heating to 220° C. and keeping it for 2 hours.

9. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The flow rate of the nitrogen gas is 80-120 mL / min.

10. The method for preparing the TiN-SiN2O ceramic modified C / C-SiC brake material according to claim 3, characterized in that: The heat treatment process is as follows: heating to 900-1000°C at a heating rate of 1-5°C / min, keeping warm for 1-2h, then heating to 1400-1500°C at a heating rate of 1-5°C / min, keeping warm for 2-3h, then cooling to 250-300°C at a cooling rate of 7-10°C / min and then cooling to room temperature with the furnace.

Citation Information

Patent Citations

  • Silicon nitride-titanium nitride bonded silicon carbide refractory material and preparation method thereof

    CN109293376A

  • C / C-SiC composite material with high strength and high friction performance and preparation method thereof

    CN116606159A

  • Si2N2O and TiN co-reinforced SiC composite refractory material and preparation method thereof

    CN117164367A

  • Ceramic-fibre composite hot gas tube - with ceramic matrix formed from silicon polymer and fibres of inorganic materials or mixts., used for e.g. vehicle exhaust tube

    DE4016052A1

  • Production of sintered ceramic

    JP1993032451A